2010
DOI: 10.1124/jpet.110.174425
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Methylphenidate Dose Response between Periadolescent and Adult Rats in the Familiar Arena-Novel Alcove Task

Abstract: Methylphenidate is a psychostimulant widely used in the treatment of attention deficit hyperactivity disorder. In this study, the effects of two nonstereotypy-inducing doses of methylphenidate (2.5 and 5.0 mg/kg s.c.) were examined in periadolescent [postnatal days (P) 35 and 42] and young adult (P70), male Long-Evans rats using a three-period locomotor activity paradigm that affords inferences about exploration, habituation, and attention to a novel stimulus (an "alcove") in a familiar environment in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…2). The dopamine levels measured in the unlesioned hemispheres were comparable to those found in previous studies (Davis et al, 2010; Kilts et al, 1981; Levant et al, 2011; Widerlöv et al, 1982). …”
Section: Resultssupporting
confidence: 89%
“…2). The dopamine levels measured in the unlesioned hemispheres were comparable to those found in previous studies (Davis et al, 2010; Kilts et al, 1981; Levant et al, 2011; Widerlöv et al, 1982). …”
Section: Resultssupporting
confidence: 89%
“…Habituation is a simple form of learning which has been used to study behavioral consequences resulting from brain lesions or pharmacological manipulations. Present results showed that the number of crosses in the open field task for control animals is lower in a second and third period of exposure, in agreement with data from the literature [23,24]. After the treatment with L-NAME a dose dependent increase in the number of crosses and rearing was recorded at the first period in juvenile rats, which may be associated with positive symptoms of the schizophrenia [25].…”
Section: Discussionsupporting
confidence: 93%
“…hyperactivity was observed over time in a familiar environment with neutral context (open field) and in a threatening environment. it is interesting to mention that the locomotor hyperactivity in children with ADhD as well as animal model of ADhD (e.g spontaneous hypertensive rats) tend to be less pronounced in novel environments than in familiar ones 14 , and for that reason the test was repeated 3 times with 7 days apart. in addition, our results are in agreement with Kubova et al 15 , which reported increased locomotor activity in rats submitted to kainic acid (KA) model at PN25 (25 day of life).…”
Section: Discussionmentioning
confidence: 99%